The Influence of Audit Procedures, Audit Fees, Time Budget Pressure, and Auditor Skepticism on Audit Quality: A Case Study during the Covid -19 Pandemic in Public Service Management - Agusiady, Raden Ricky; Ismail, Muhammad Taofik; Avianty, R. Rita (Universitas Padjadjaran, 2024)
This study investigates the effects of audit processes, audit fees, time budget pressure, and auditor skepticism on audit quality in the context of public service administration during the COVID-19 pandemic. Employing a descriptive associative approach, this research uses a questionnaire for primary data collection, complemented by path analysis as the statistical method. Data sources include primary data from survey responses and secondary data from books, journals, and other scholarly sources. The study focuses on 41 Public Accounting Firms (KAP) in Bandung area, with a sample of 37 respondents as the unit of analysis. Results will be interpreted through path analysis. The research reveals that the audit situation during the COVID-19 pandemic acts as a linking variable between the independent variables (audit processes, audit fees, time budget pressure, and auditor skepticism) and audit quality. This study emphasizes the critical role of auditor professionalism and skepticism in maintaining the reliability of audit results under crisis conditions. By enhancing understanding of audit dynamics during the pandemic and strengthening auditor capabilities to manage external pressures, this study aims to improve transparency and accountability in the public service sector.